1976
DOI: 10.1159/000149972
|View full text |Cite
|
Sign up to set email alerts
|

An Immunofluorescence Technique with Counterstain on Fixed Cells for the Detection of Antibodies to Human Herpesviruses; Antibody Patterns in Patients with Hodgkin’s Disease and Nasopharyngeal Carcinoma

Abstract: An indirect immunofluorescence (IF)1 test on fixed cells with Evans’ blue counterstain is described for all four human herpesviruses, i.e., herpes simplex virus type 1 and type 2 (HSV-1 and HSV-2), varicella-zoster virus (VZV), cytomegalovirus (CMV) and Epstein-Barr virus (EBV). Comparison with immunodiffusion (ID) for HSV-2 and with ID and complement fixation (CF) for VZV and CMV demonstrated the specificity and high sensitivity of the IF test. Also introduced is a modification of the anti-complement immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1981
1981
1997
1997

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Langenhuysen et al (1974) reported that CMV antibody titers were significantly elevated in adults with Hodgkin's disease compared with healthy individuals matched for age and sex. However, in a number of other studies, no difference has been found in the incidence or magnitude of CMV antibody titers between patients with Hodgkin's disease (Levine et al, 1971;Andersen et al, 1976;Hilgers and Hilgers, 1976), non-Hodgkin's Iymphomas (Andersen et al, 1976;Dumont et al, 1976), or leukemias (Andersen et al, 1976) and normal controls. These results, taken together with those of Duvall et al (1966), may indicate that in adults with neoplasia, most of whom are seropositive, little difference in antibody status is appreciated compared to the population at large.…”
Section: Cytomegalovirus Lnfection In Adults With Malignanciesmentioning
confidence: 92%
“…Langenhuysen et al (1974) reported that CMV antibody titers were significantly elevated in adults with Hodgkin's disease compared with healthy individuals matched for age and sex. However, in a number of other studies, no difference has been found in the incidence or magnitude of CMV antibody titers between patients with Hodgkin's disease (Levine et al, 1971;Andersen et al, 1976;Hilgers and Hilgers, 1976), non-Hodgkin's Iymphomas (Andersen et al, 1976;Dumont et al, 1976), or leukemias (Andersen et al, 1976) and normal controls. These results, taken together with those of Duvall et al (1966), may indicate that in adults with neoplasia, most of whom are seropositive, little difference in antibody status is appreciated compared to the population at large.…”
Section: Cytomegalovirus Lnfection In Adults With Malignanciesmentioning
confidence: 92%
“…The development of EBNA after infection was monitored by the appearance of the typical immunofluorescence pattern of the anti-complement immunofluorescence test of Reedman and Klein (1973) slightly modified as described earlier (Hilgers and Hilgers, 1976). To exclude false positives we made sure to use anti-nuclear factor-negative serum.…”
Section: Ebnamentioning
confidence: 99%
“…Τέλος όσον αφορά την σχέση της νόσου του Hodgkin με ιογενείς παράγοντες, υ πάρχουν αναφορές, οι οποίες δείχνουν αυξημένο τίτλο αντισωμάτων σε ασθενείς με νόσο του Hodgkin έναντι του ιού των Epstein-Barr, του ιού του έρπητα ζω στήρα ή του απλού έρπητα (Stepina et al 1976, Holy et al 1977, Hilgers and Hilgers 1976. Σημειώνεται επίσης ότι οι ασθενείς με υψηλό τίτλο αντισωμά των κατά του ιού των Epstein-Barr έδειξαν άλλοτε εξασθενημένη κυτταρική α νοσία (Johansson et al 1975)και άλλοτε αυξημένη κυτταρική ανοσία (Chan et al 1977).…”
Section: Hodgkinunclassified